Percepções sobre saúde mental, suicídio e o comportamento autolesivo no contexto escolar sob a ótica dos estudos culturais - TAMIRES VILA MAIOR (2021)
This research starts from the eagerness for answers in face of perceptions about the mental frailty of high school students, when realizing that they, in general, suffered from certain situations both at home and at school, I felt obliged to create projects and places of speech so that they could manifest themselves in some way. From then on, an interdisciplinary project called “Favorable Chat” was created, including student teachers and other invited professionals. The project was conceived and put into practice and aimed to work on the new subjects proposed by the Common National Curriculum Base (BNCC) and would involve socio-emotional skills. Therefore, this research seeks to investigate the mental health, suicide, self-harm behavior and cultural perceptions of education professionals and high school students in a public school in the city of Aquidauana, state of Mato Grosso do Sul, Brazil. Data analysis is based on cultural studies theorists and on the comparison of bibliography on mental health and suicide. The aim of this study is to analyze how the school and students perceive suicide and propose ways to improve the mental health of students in the school environment, with a view to promoting life. Qualitative, exploratory-descriptive research, using bibliographic techniques; semi-structured interviews with education professionals, namely: school unit director, teachers and student inspector; observation and formation of discussion groups and production of materials for students aged 14 to 17 through illustrations. The results indicate that it is possible to infer that both the school and the students need to talk more about the topic, in order to break with myths and clarify other ways to solve problems that promote discussions and production of materials on mental health and the promotion of life in the entire school community involved.